S20. SCREENING FOR THE AT-RISK MENTAL STATE IN EDUCATIONAL SETTINGS: A SYSTEMATIC REVIEW. (9th April 2019) - Howie, Clare; Potter, Claire; Shannon, Ciaran; Davidson, Gavin; Mulholland, Ciaran
Abstract: Background: The at-risk mental state provides a model which can allow clinicians to identify individuals at-risk of developing psychosis and intervene to prevent or delay onset. Early intervention is linked with better prognosis and recovery. At present, most screening is carried out within help-seeking populations, however screening within educational settings may allow clinicians to identify individuals at-risk earlier. This is a systematic narrative review examining the screening tools that have been used in educational settings, with three key questions. Can screening in this setting detect individuals at-risk? What screening tools have been used in educational settings? Are there differences in threshold scores in screening tools in this context? Methods: Searches were carried out on PsycINFO, MEDLINE, EMBASE, Scopus and Web of Science. The searches aimed to find any articles that detailed screening procedures for the at-risk mental state carried out within educational settings. Inclusion criteria were studies that were carried out in educational settings using a screening measure for attenuated psychotic symptoms with a follow-up assessment to assess for the at-risk mental state. All study types were included. Studies that did not include these three criteria were excluded. Results: 2097 references were identified for title and abstract screening. 104 articles were identified for screening by full-text. 11 articles are included in the review. Data extraction was completed using an adapted version of the template from the Cochrane Collaboration Data Collection Form for Intervention Reviews: RCTs and non-RCTs. Discussion: The PQ-16 is the most commonly used screening measure in educational settings such as colleges and university settings and secondary schools. A full review will be presented and the potential benefits of identifying young people at risk of psychosis in educational settings will be discussed.